2021
DOI: 10.1177/24705470211030273
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain is Associated With Reduced Sympathetic Nervous System Reactivity During Simple and Complex Walking Tasks: Potential Cerebral Mechanisms

Abstract: Background Autonomic dysregulation may lead to blunted sympathetic reactivity in chronic pain states. Autonomic responses are controlled by the central autonomic network (CAN). Little research has examined sympathetic reactivity and associations with brain CAN structures in the presence of chronic pain; thus, the present study aims to investigate how chronic pain influences sympathetic reactivity and associations with CAN brain region volumes. Methods Sympathetic reactivity was measured as change in skin condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
(54 reference statements)
0
11
0
1
Order By: Relevance
“…It has also been proposed that sympathetic tone is increased in osteoarthritis patients. 25,26 In these chronic musculoskeletal conditions, as in TMD, it remains unclear whether pain drives increased sympathetic tone or increased sympathetic tone results in pain.…”
Section: Autonomic Changes In Other Chronic Musculoskeletal Pain Cond...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed that sympathetic tone is increased in osteoarthritis patients. 25,26 In these chronic musculoskeletal conditions, as in TMD, it remains unclear whether pain drives increased sympathetic tone or increased sympathetic tone results in pain.…”
Section: Autonomic Changes In Other Chronic Musculoskeletal Pain Cond...mentioning
confidence: 99%
“…This study also looked at sympathetic efferent discharge in the peroneal nerve and reported that it was positively correlated with pain intensity. It has also been proposed that sympathetic tone is increased in osteoarthritis patients 25,26 . In these chronic musculoskeletal conditions, as in TMD, it remains unclear whether pain drives increased sympathetic tone or increased sympathetic tone results in pain.…”
Section: Physiological Evidencementioning
confidence: 99%
“…Chronic pain often results from a depletion of the sympathetic nervous system (Ref. 32), and endometriosis also causes CPP. Although its mechanism is unclear, it encourages researchers to study the links between nerve change, inflammation and immune dysfunction (Refs 25, 33).…”
Section: Neurogenesis and Endometriosismentioning
confidence: 99%
“…Hallazgos de investigación básica de carácter anatómico describen la existencia de proyecciones nociceptivas directas del tracto espinotalámico hacia áreas motoras (Dum et al, 2009), por otra parte, existe evidencia que sugiere que los correlatos neurales implicados en la experiencia dolorosa incluyen la actividad relacionada con los procesos perceptivos, los motores y la actividad de sistema nervioso autónomo (Piché et al, 2010;Tiemann et al, 2018;Yeater et al, 2021). Otros autores describen, que los estímulos nociceptivos mantenidos pueden evocar una inhibición de la corteza motora generando alteraciones en la actividad neuromuscular, este proceso puede incrementar la actividad del sistema nervioso simpático y alterar el funcionamiento de vías aferentes (propiocepción, procesamiento somatosensorial) implicadas en el movimiento (Nijs et al, 2012).…”
Section: El Sustrato Neural De La Dimensión Del Comportamiento Motorunclassified